The problem of appetite loss after major abdominal surgery: a systematic review - Wagner, Martin; Probst, Pascal; Haselbeck-Köbler, Michael; Brandenburg, Johanna; Kalkum, Eva; Störzinger, Dominic; Keßler, Jens; Simon, Joe J.; Friederich, Hans-Christoph; Angelescu, Michaela; Billeter, Adrian; Hackert, Thilo; et al. (Annals of surgery, 2022)
OBJECTIVE: To systematically review the problem of appetite loss after major abdominal surgery. - SUMMARY OF BACKGROUND DATA: Appetite loss is a common problem after major abdominal surgery. Understanding of etiology and treatment options is limited. - METHODS: We searched Medline, Cochrane Central Register of Controlled Trials, and Web of Science for studies describing postoperative appetite loss. Data were extracted to clarify definition, etiology, measurement, surgical influence, pharmacological, and nonpharmacological treatment. PROSPERO registration ID: CRD42021224489. - RESULTS: Out of 6144 articles, we included 165 studies, 121 of which were also analyzed quantitatively. A total of 19.8% were randomized, controlled trials (n = 24) and 80.2% were nonrandomized studies (n = 97). The studies included 20,506 patients undergoing the following surgeries: esophageal (n = 33 studies), gastric (n = 48), small bowel (n = 6), colon (n = 27), rectal (n = 20), hepatobiliary (n = 6), and pancreatic (n = 13). Appetite was mostly measured with the Quality of Life Questionnaire of the European Organization for Research and Treatment of Cancer (EORTC QLQ C30, n = 54). In a meta-analysis of 4 randomized controlled trials gum chewing reduced time to first hunger by 21.2hours among patients who had bowel surgery. Other reported treatment options with positive effects on appetite but lower levels of evidence include, among others, intravenous ghrelin administration, the oral Japanese herbal medicine Rikkunshito, oral mosapride citrate, multidisciplinary-counseling, and watching cooking shows. No studies investigated the effect of well-known appetite stimulants such as cannabinoids, steroids, or megestrol acetate on surgical patients. - CONCLUSIONS: Appetite loss after major abdominal surgery is common and associated with increased morbidity and reduced quality of life. Recent studies demonstrate the influence of reduced gastric volume and ghrelin secretion, and increased satiety hormone secretion. There are various treatment options available including level IA evidence for postoperative gum chewing. In the future, surgical trials should include the assessment of appetite loss as a relevant outcome measure.